The complete chloroplast genome of Populus xiangchengensis, an endemic species in Southwest China - Dan Zong; Anpei Zhou; Dan Li; Chengzhong He (Mitochondrial DNA. Part B. Resources, 2019)
The complete chloroplast genome sequence of Populus xiangchengensis C. Wang et Tung, an endemic species in southwest China, is presented in this study. The total genome size is 156,465 bp, with a typical quadripartite structure including a pair of inverted repeat (IRs, 27,570 bp) regions separated by a large single copy (LSC, 84,812 bp) region and a small single copy (SSC, 16,513 bp) region. The overall GC content of P. xiangchengensis plastid genome is 36.74%. The genome contains 130 genes, including 85 protein-coding genes, 37 transfer RNA genes, and eight ribosomal RNA genes. Among these genes, 12 genes have one intron and three genes contain two introns. The phylogenetic tree based on 26 complete plastomes of Salicaceae support close relationships among P. xiangchengensis, P. cathayana, and P. szechuanica.